2022
DOI: 10.1007/s11356-022-21723-8
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based time series models for effective CO2 emission prediction in India

Abstract: As per the report of datacommons.org, ๐ถ๐‘‚ 2 emission in India is 1.80 metric tons per capita, which is very harmful for living beings. So, this paper presents India's detrimental ๐ถ๐‘‚ 2 emission effect with the prediction of ๐ถ๐‘‚ 2 emission for the next ten years based on univariate time series data. We used three statistical models i.e., AutoRegressive Integrated Moving Average (ARIMA) model, Seasonal AutoRegressive Integrated Moving Average with eXogenous factors (SARIMAX) model, and Holt-Winter model, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…PM exposure has become a global challenge, accounting for 8.8 million deaths annually across the world (Li et al 2015). Rigorous anthropogenic activities resulting in poor air quality have drawn worldwide attention in recent decades, especially in Asian nations (Li et al 2016;Naqvi et al 2020;Bilal et al 2021;Kumari and Singh 2022). Atmospheric PM 2.5 continues to pique attention worldwide because of its substantial impacts on human health, the environment, and welfare (Valavanidis et al, 2008;Hassanen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…PM exposure has become a global challenge, accounting for 8.8 million deaths annually across the world (Li et al 2015). Rigorous anthropogenic activities resulting in poor air quality have drawn worldwide attention in recent decades, especially in Asian nations (Li et al 2016;Naqvi et al 2020;Bilal et al 2021;Kumari and Singh 2022). Atmospheric PM 2.5 continues to pique attention worldwide because of its substantial impacts on human health, the environment, and welfare (Valavanidis et al, 2008;Hassanen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Before introducing the structure for this paper, some other articles applied similar methods to analyze the CO2 emission data. For example, Kumar et al mainly applied time series analysis and machine learning prediction models to analyze and predict future air quality [5]. Since CO 2 is one of the most critical factors, the CO2 emission has also been forecasted using ARIMA and linear regression model [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kumar et al mainly applied time series analysis and machine learning prediction models to analyze and predict future air quality [5]. Since CO 2 is one of the most critical factors, the CO2 emission has also been forecasted using ARIMA and linear regression model [5]. Besides, Nyoni et al have also applied time series models, e.g., the ARIMA prediction model, to forecasting CO 2 emissions in China [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant findings include that the overall CO2 emissions in India are projected to rise 2915 million tons by 2020. In 2022 [9], Surbhi Kumari and Sunil Kumar Singh addressed the problem for accurate Prediction of CO2 emission in India by applying three models LSTM, SARIMAX, and Holt-Winters model on 40 years of CO2 emission data. They concluded that LSTM is the best performing model for CO2 emission Prediction.…”
mentioning
confidence: 99%